2019
DOI: 10.3390/vetsci6010004
|View full text |Cite
|
Sign up to set email alerts
|

Heat Stress Modulates Brain Monoamines and Their Metabolites Production in Broiler Chickens Co-Infected with Clostridium perfringens Type A and Eimeria spp.

Abstract: Heat stress has been related to the impairment of behavioral and immunological parameters in broiler chickens. However, the literature is not clear on the involvement of neuroimmune interactions in a heat stress situation associated with bacterial and parasitic infections. The present study evaluated the production of monoamines and their metabolites in brain regions (rostral pallium, hypothalamus, brain stem, and midbrain) in broiler chickens submitted to chronic heat stress and/or infection and co-infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
2
8
0
1
Order By: Relevance
“…In a study with broiler chickens, heat stress and/or intestinal infection with Clostridium and Eimeria spp. (bacteria and protozoal species, respectively) led to changes in concentrations of monoamines in key brain regions, including a decrease in 5-HT, NE, and E in the hypothalamus, and dopamine in the mid-brain ( Calefi et al, 2019 ). Authors speculated that these data demonstrated activation of the HPA axis via increased release of cytokines from intestinal immune cells, in response to the pathogen challenge.…”
Section: Heat Stress Activates the Hpa Axismentioning
confidence: 99%
“…In a study with broiler chickens, heat stress and/or intestinal infection with Clostridium and Eimeria spp. (bacteria and protozoal species, respectively) led to changes in concentrations of monoamines in key brain regions, including a decrease in 5-HT, NE, and E in the hypothalamus, and dopamine in the mid-brain ( Calefi et al, 2019 ). Authors speculated that these data demonstrated activation of the HPA axis via increased release of cytokines from intestinal immune cells, in response to the pathogen challenge.…”
Section: Heat Stress Activates the Hpa Axismentioning
confidence: 99%
“…Furthermore, it is believed that serotonin regulates the process of bone formation, as well as the mechanism of bone resorption [ 15 ]. In this context, Calefi et al [ 16 ] reported that acute stress conditions such as environmental temperature increases the concentration of serotonin in brain tissues; however, chronic stress conditions decrease the level of brain serotonin. Therefore, the aim of the current work is to analyze changes in the brain serotonin, liver CoQ10, energy metabolism, antioxidant biomarkers, and blood chemistry of broiler chickens subjected to chronic thermal stress.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, activation of the HPA axis leads to sickness behavior in chickens, owing to elevated cortisol secretion. A combination of decreased feed intake, weight loss, decreased movement, and increased sleepiness is considered as sickness behavior in chickens [36]. Proposed gut-brain axis model for chickens.…”
Section: Gut-brain Axis and Gut Healthmentioning
confidence: 99%
“…Thus, signals may transduce to the brain and influence cognition and behavior or cause changes in the enteric system and provide feedback on the microbiota. Calefi et al [36] analyzed the neurochemical profile in the hypothalamus, midbrain, and brainstem of broiler chickens exposed to Eimeria spp., Clostridium perfringens (C. perfringens), and heat stress. The findings of this study showed that exposure to C. perfringens elevates the dopamine levels in the hypothalamus, rostral pallium, and midbrain.…”
Section: Gut-brain Axis and Gut Healthmentioning
confidence: 99%